Match-Play External Load and Internal Load in NCAA Division II Women's Soccer - Choice, Erin E; Tufano, James J; Jagger, Kristen L; Cochrane-Snyman, Kristen C (Journal of strength and conditioning research, 2023)
Choice, EE, Tufano, JJ, Jagger, KL, and Cochrane-Snyman, KC. Match-play external load and internal load in NCAA Division II women's soccer. J Strength Cond Res 37(12): e633-e639, 2023-The purpose of this study was to describe average match-play demands for NCAA DII women's soccer, including positional and time-specific differences, and relationships between variables. External load was assessed using total distance, relative distance, sprint distance, number of power plays, peak speed, and Player Load. Internal load was assessed using session rating of perceived exertion (sRPE). Mixed factor analysis of variance was used to assess time by position (midfielder, forward, or defender) for dependent measures. Correlations were assessed between separate pair groups. Average match-play demands included 9,463 ± 2,591 m total distance, 172 ± 48 m·min -1 relative distance, 531 ± 301 m sprint distance, peak speeds of 26 ± 1.6 kph, 46.71 ± 21.75 power plays, and 457.84 ± 121.78 AU Player Load. Significant ( p < 0.05) positional differences were found for total distance, Player Load, match load, and peak speed. Significant, moderate correlations were found between relative distance and match load, and sRPE and total distance, Player Load, and power plays (all p < 0.001). Results indicate there are positional differences within a women's DII soccer team, with midfielders accumulating the longest distances (10,509 ± 2,913 m) and greatest Player Load (527.79 ± 130.5 AU) and match load (576 ± 343 AU), forwards running the fastest peak speeds (26.8 ± 1.5 kph), and defenders maintaining most consistent performance. Match-play external and internal load data should be monitored by player position and half for DII women's soccer.
Keywords: fotbal; Soccer; Geographic Information Systems; Humans; Athletic Performance; lidé; Female; geografické informační systémy; ženské pohlaví; sportovní výkon